Effects of Changes in Runoff Characteristics on Asphalt Mixtures' Performance Against Low-Temperature Cracking - Mehdi Mehdinazar; Ali Abdi Kordani; Mahyar Arabani (Results in Engineering)
When runoff is exposed to pavement surface contamination, its characteristics change; as a result, runoff can have a more severe destructive impact on the pavement's performance against cracking. Accordingly, this research examined the result of runoff acidity variations on the performance of different hot-mix asphalt samples against low-temperature cracking. Two performance grade bitumens (PG 64-16 and PG 58-22), each modified with two percentages of Zeolite, along with two aggregates with different moisture performances (limestone and siliceous), were employed. These 12 HMA samples were subjected to environmental conditions with acidity levels of 5, 6, 7, 8, and 9. Then, rheological tests (bending beam rheometer) were performed on the control and modified bitumens; mechanical tests (semicircular bending beam) were conducted on asphalt mixture specimens; and thermodynamic tests (Universal Sorption Device and Wilhelmy Plate) were executed on the aggregates and bitumens to determine the surface free energy elements, respectively. Applying environmental conditions raised the low-temperature cracking potential of asphalt mixtures up to 32%. Zeolite elevated the rate of stress relaxation and lowered the stiffness of the bitumens. Environmental conditions also raised the debonding energy up to 12%., which increased the system's tendency to bitumen-aggregate debonding, demonstrating a more destructive impact in acidic conditions. According to the mechanical test results, placing the HMA samples in acidic or basic runoff conditions significantly decreased fracture energy and fracture toughness. Zeolite increased fracture toughness and fracture energy in acidic and basic environmental conditions up to 25%.